2020
DOI: 10.1002/admi.201901663
|View full text |Cite
|
Sign up to set email alerts
|

Simplified All‐Solid‐State WO3 Based Electrochromic Devices on Single Substrate: Toward Large Area, Low Voltage, High Contrast, and Fast Switching Dynamics

Abstract: Electrochromic devices (ECDs) represent one of the most promising energy saving and solar control technology for the market of energy‐efficient building and optoelectronic devices. A continuous and intense effort is currently devoted to the development of effective solid‐state ECDs and their integration in multifunctional systems, such as photoelectrochromics. Here, the fabrication of simplified all‐solid‐state WO3 based ECDs on single‐substrate is reported, demonstrating how the rational design of highly inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 52 publications
(205 reference statements)
3
39
0
Order By: Relevance
“…As stated before, the research in electrofluorochromism is at a relatively early stage compared to other fields performing the electrochemical manipulation of optical properties, such as electrochromism [37][38][39][40][41][42][43][44][45] or electrochemiluminescence. [46] Electrofluorochromism, that is, the electrochemical switching of fluorescence, usually concerns organic or organometallic molecular systems, broadly classifiable as switchable molecular dyads and intrinsically switchable electroactive fluorophores (either small molecules or conjugated polymers).…”
Section: Conventional Mechanisms Of Electrofluorochromism: Molecular mentioning
confidence: 99%
“…As stated before, the research in electrofluorochromism is at a relatively early stage compared to other fields performing the electrochemical manipulation of optical properties, such as electrochromism [37][38][39][40][41][42][43][44][45] or electrochemiluminescence. [46] Electrofluorochromism, that is, the electrochemical switching of fluorescence, usually concerns organic or organometallic molecular systems, broadly classifiable as switchable molecular dyads and intrinsically switchable electroactive fluorophores (either small molecules or conjugated polymers).…”
Section: Conventional Mechanisms Of Electrofluorochromism: Molecular mentioning
confidence: 99%
“…[25] On the contrary, we reported a simplified device entirely manufactured at room temperature conditions and continuously on a single substrate without, however, any extra UV curing or annealing treatment of the polymer electrolyte. [28,5] In this case, in a similar way to the all-inorganic devices, the top electrode acts as a sealant through the direct deposition of a highly transparent indium tin oxide (ITO) electrode atop of the EC film. The active EC layer is based on well-interconnected tungsten oxide (WO 3 ) columnar nanostructures with a polymer electrolyte matrix (Nafion).…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of the electrochromic/electrolyte interface enabled lower activation voltages (0.5–3 V) and faster switching kinetics (5–10 s) if compared to all‐solid‐state devices based on both bulk and mesoporous WO 3 . [ 28 ] In addition, apart from providing higher transmittance in bleached state, this type of device exhibits a wide optical contrast (Δ T = 70%) and high coloration efficiency. Recently, such a simplified EC unit was successfully integrated with semitransparent perovskite photovoltaic cells demonstrating for the first time the realization of highly efficient all‐solid‐state photovoltachromic smart windows on a single glass.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Overall consideration on production cost, coloration efficiency, response speed and cycle durability suggests that tungsten trioxide (WO3) is the most preferred candidate for large-scale application of electrochromic devices (ECDs). [5][6][7] Previous works suggested that when small ions such as H + , Li + , Na + or Al 3+ are inserted into the WO3 lattice, transitions between small-polaron states associated with W ions of different valences could result in optical absorptions that are responsible for coloration of WO3. [8][9][10][11] The reversible injection and extraction of the extrinsic ions as controlled by electric field form the basic mechanism of a WO3-based ECD.…”
Section: Introductionmentioning
confidence: 99%